The equation that is the same as y = 3 cos(2 (x + π/2)) - 2 is y = -3 sin (2(x + π/4)) -2
We have the original equation as;
y = 3 cos(2 (x + π/2)) - 2
The sine and cosine functions are related by the formula;
cos(θ) = sin (π/2 - θ)
Hence;
y = 3 cos(2 (x + π/2)) - 2
y = 3 cos(2x + π) - 2
When θ = 2x + π, it follows that:
cos(2x + π) = sin (π/2- (2x + π))
= sin (-2(x + π/4))
Since
sin(-θ) = -sin (θ)
Then:
sin (-2(x + π/4)) = -sin (2(x + π/4))
So
sin (2(x + π/4)) = cos(2x + π)
Finally;
y = -3 sin (2(x + π/4)) -2
Learn more about equivalent equation:https://brainly.com/question/16905759
#SPJ2